Karakter Santri Pondok Pesantren Fathul ‘Ulum Jombang - Indana, Nurul; Annisa At-Taqiyah, Farah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to describe the character of the students and the factors that influence the character building of the students at Pondok Pesantren Fathul 'Ulum Jombang. The method is descriptive qualitative. The data collection techniques used are structured interviews, non-participant observation, and documentation. Data were analysed by condensing data, presenting data, verifying and concluding. Data validity testing techniques with extended observation, triangulation, member check. The results of research in the field show that, the character of students at Fathul 'Ulum Jombang Islamic Boarding School There are three main aspects that support communication (honesty, discipline and responsibility). The main factors that play an important role in shaping the character of students, namely biological factors, environmental factors and communication factors.